Microbial culturomics: The next generation culture for identification of the human gastrointestinal microbiota - Noha Mostafa Mahmoud (Novel Research in Microbiology Journal, 2023)
The maintenance of human health and the development of disease are both significantly influenced by the gut microbiota. The development of omics technologies improves the understanding of the gut microbial ecosystem. Metagenomics has emphasized the diversity of the gut microbiome; however, it does not provide reliable insight on the dark matter of microorganisms or the minor populations. As a result of the rebirth of cultural techniques in microbiology; the field of "culturomics" is created to cultivate the unidentified bacteria that reside inside the human gut. In the 21st century's discipline of clinical microbiology; microbial culturomics becomes a promising strategy that may be used to cultivate hundreds of novel microorganisms linked to human; thus, opening new insights on the host-microbial relationships. Novel taxa and species will be detected by optimizing the culture conditions; followed by quick identification using mass spectrometry or molecular next generation sequencing. Culturomics of the human gut microbiota can be used as a bactriotherapy for the inflammatory bowel diseases and the respiratory illnesses like COVID-19, and as an immunomodulatory agent for cancer therapy. Furthermore, culturomics is a big store for discovering new antibacterial agents and resistance genes. The aim of this review was to highlight the background; methodologies, and future use of culturomics to study the human gut microbiota.